Optimizing Sales of Candied Mangoes through Digital Martketing on the Whatsapp Business Platform - Nur Intan; Dedu, May (Indonesian Journal of Business Analytics, 2024)
This research aims to investigate the potential for optimizing sales of candied mango fruit through digital marketing strategies using the WhatsApp Business platform. With the emergence of information and communication technology, the use of digital platforms has become important for small and medium businesses, including candied fruit producers. This research uses a qualitative approach with in-depth interviews and observations of mango candied producers who have implemented WhatsApp Business in their marketing strategy. The collected data was analyzed using the content analysis method. The research results show that using WhatsApp Business can increase consumer accessibility to candied mango products. Through features such as product catalogs, automated messages, and discussion groups, manufacturers can effectively communicate product information to potential customers. Additionally, WhatsApp Business enables direct interaction between manufacturers and customers, which can increase customer trust and loyalty. However, challenges faced include the need to ensure consistent product availability and quality, as well as managing orders efficiently. This research concludes that using WhatsApp Business as a digital marketing platform can be an effective strategy for candied mango producers to increase sales and expand their market reach.